Development and Validation of A Questionnaire Assessing Challenges and Competencies of Crisis Leadership in The Public Healthcare System - Nachia Banu Abdul Rahim; Fredie Robinson; Aizuddin Hidrus; Rudi Nasib; Abraham En Loong Chiu; Primus John; Prabakaran Solomon Dhanaraj (Asia Pacific Journal of Health Management)
Introduction: During the pandemic, crisis leadership is being tested in ways the world hasn’t seen in generations, and leading through it has become a severe challenge for leadership in public health organisation. Therefore, this study aims to develop and validate a self-administered questionnaire (Crisis Leadership Questionnaire, CLQ) to assess the challenges and competencies faced and needed in crisis leadership.